Dual-function desulfurization catalyst and its preparation method and application

By modifying activated carbon, a dual-function desulfurization catalyst with rich active sites and alkaline centers is formed, which solves the problems of low cost and low desulfurization efficiency in the prior art, and achieves an efficient and economical flue gas desulfurization effect.

CN118950087BActive Publication Date: 2025-03-14成都达奇科技股份有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411442507.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-03-14
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing dual-function desulfurization catalysts have problems of low cost and low desulfurization efficiency.

Method used

By impregnating activated carbon in a modified solution containing urea, soluble copper salt, iron salt and zinc salt, and subsequently heat treatment is performed, a bifunctional desulfurization catalyst with rich active sites and alkaline centers is formed.

Benefits of technology

The synchronous removal of COS and H2S is achieved, which improves the desulfurization efficiency, reduces operating costs, and has good oxidation resistance and anti-sulfur poisoning ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118950087B_ABST
    Figure CN118950087B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of flue gas desulfurization, discloses a dual-function desulfurization catalyst and its preparation method and application, and solves the technical problems of low cost and low desulfurization efficiency of dual-function desulfurization catalyst in the prior art. The dual-function desulfurization catalyst is used to remove COS and H2S in flue gas at low temperature. The preparation method of the dual-function desulfurization catalyst includes the following steps: impregnating activated carbon in a first modification solution, filtering, drying and heat-treating after the impregnation is completed; the first modification solution contains urea and at least one of soluble copper salt, iron salt and zinc salt; impregnating activated carbon in a second modification solution, filtering, drying and heat-treating after the impregnation is completed, and obtaining a dual-function desulfurization catalyst; the second modification solution contains alkali metal salt and / or alkali.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flue gas desulfurization, and in particular to a dual-function desulfurization catalyst and a preparation method and application thereof. Background Art

[0002] Carbonyl sulfide (COS) is a common toxic and harmful component in industrial gases such as blast furnace gas, yellow phosphorus tail gas, and closed calcium carbide furnace tail gas. The presence of trace amounts of COS will affect the utilization of tail gas resources, deactivate catalysts, corrode reaction equipment, and affect reaction rates. Therefore, effective removal of COS is a key research direction in the industrial and environmental fields. At present, the most commonly used COS removal process is a two-stage method, that is, COS is first converted into H2S by catalytic hydrolysis, and then H2S is removed by adsorption or catalytic oxidation. However, the subsequent treatment of H2S produced during the COS hydrolysis process makes the two-stage method have a long operation process, greater cost, and excessively high costs.

[0003] The Chinese invention patent with announcement number CN114768875A discloses a blast furnace gas desulfurization catalyst and a blast furnace gas desulfurization process, which uses a transition metal phthalocyanine complex as a main catalyst and a co-catalyst to effectively convert organic sulfur into inorganic sulfur. The desulfurization efficiency can reach more than 85%, but the catalyst preparation process is loaded, the desulfurization process generates a large amount of wastewater, and the material cost investment and desulfurization operation cost are relatively high.

[0004] Chinese invention patent application with publication number CN11782989A discloses a method for preparing a bifunctional aluminum-based desulfurization catalyst for the simultaneous and efficient removal of organic sulfur and H2S. A catalyst precursor is obtained from γ-Al2O3, an active component and an auxiliary component by a dispersion precipitation method, and then a bifunctional aluminum-based desulfurization catalyst is prepared by kneading, molding, drying and calcining. The bifunctional aluminum-based desulfurization catalyst can achieve the simultaneous removal of COS and H2S, but due to the limited specific surface area and pore volume of alumina, there is still a problem of low desulfurization efficiency.

[0005] In summary, the current bifunctional desulfurization catalysts have the disadvantages of low cost and low desulfurization efficiency. Summary of the invention

[0006] The main purpose of the present invention is to provide a bifunctional desulfurization catalyst and a preparation method and application thereof, so as to solve the technical problems of low cost and low desulfurization efficiency of the bifunctional desulfurization catalyst in the prior art.

[0007] In order to achieve the above object, according to the first aspect of the present invention, a method for preparing a bifunctional desulfurization catalyst is provided, and the technical scheme is as follows:

[0008] A method for preparing a bifunctional desulfurization catalyst, wherein the bifunctional desulfurization catalyst is used for removing COS and H2S from flue gas at low temperature, and the preparation method comprises the following steps:

[0009] The activated carbon is immersed in a first modification solution, and after the immersion is completed, the activated carbon is filtered, dried and heat-treated; the first modification solution contains urea and at least one of a soluble copper salt, an iron salt and a zinc salt;

[0010] The activated carbon is impregnated in a second modified solution, and after the impregnation, it is filtered, dried and heat-treated to obtain a bifunctional desulfurization catalyst; the second modified solution contains an alkali metal salt and / or a base.

[0011] The preparation method of the bifunctional desulfurization catalyst of the present invention has the following advantages:

[0012] Urea is coupled with activated carbon to produce pyridinic N. The nucleophilic nature of pyridinic N enhances the moderately alkaline active sites of the catalyst, enhancing the adsorption and reactivity to acidic gases (such as H2S). Due to the nucleophilic nature of pyridinic N, the protons of H2O are attacked, resulting in a strong dissociation of H2O to generate alkaline -OH that promotes the hydrolysis of COS. Pyridinic N forms cavity sites that can serve as metal oxide anchoring points, inducing the metal oxide to be highly dispersed on the catalyst surface, thereby exposing more active sites and producing abundant reactive oxygen to promote H2S oxidation.

[0013] Soluble copper salts, iron salts and zinc salts will decompose and transform into corresponding metal oxides during the subsequent heat treatment process. The metal oxides evenly distributed on the surface of activated carbon play a key catalytic role, which helps to improve the adsorption and reaction capacity of COS and H2S. In particular, through the combined action of metal salts and urea, the surface of the modified activated carbon can form more abundant active sites and alkaline centers, enhancing the synergistic removal capacity of COS and H2S.

[0014] Alkali metal salts and alkalis such as sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate and other alkaline substances can significantly increase the alkalinity of the activated carbon surface, making it more conducive to adsorption and reaction with acidic gases (such as H2S) to form sulfides, reducing H2S emissions; alkaline modification helps to improve the catalyst's antioxidant and sulfur poisoning resistance and extend its service life; alkaline modification can make the catalyst easier to restore activity during the regeneration process, thereby improving its economy and sustainability in long-term use.

[0015] It can be seen that the bifunctional desulfurization catalyst prepared by the present invention can remove COS and H2S in one step, with high desulfurization efficiency and no secondary pollution. It has been verified that the obtained bifunctional desulfurization catalyst has strong adaptability to fluctuating reaction conditions, exhibits excellent bifunctional catalytic performance in a slightly oxidized and humid atmosphere, has good potential to replace the existing two-stage process, and is expected to provide huge environmental and economic benefits.

[0016] As a further improvement of the preparation method of the above-mentioned bifunctional desulfurization catalyst: the mass ratio of nitrogen element to metal element in the first modified solution is (1-3):1, and the concentration of nitrogen element is 30-60 g / L; the activated carbon is immersed in the first modified solution for 1-3 hours by an equal volume impregnation method; the heat treatment temperature is 400-600°C, and the heat treatment time is 1-5 h.

[0017] As a further improvement of the preparation method of the above-mentioned bifunctional desulfurization catalyst: the mass ratio of alkali metal salt and / or base to activated carbon in the second modified solution is (1.5-3.5):100; the activated carbon is immersed in the second modified solution for 0.5-12 hours by an equal volume impregnation method; the heat treatment temperature is 120-200°C, and the heat treatment time is 3-24 hours; the second modified solution contains at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.

[0018] As a further improvement of the preparation method of the above-mentioned bifunctional desulfurization catalyst: it also includes the steps of: immersing the activated carbon in a third modified solution, filtering and drying after the immersion is completed; the third modified solution contains a first active component and / or a second active component, the first active component is tea polyphenols and / or caffeine, and the second active component is a flavonoid compound or a glycoside of a flavonoid compound.

[0019] As a further improvement of the preparation method of the above-mentioned bifunctional desulfurization catalyst: the mass of the first active component in the third modified solution is 1-2% of the mass of the activated carbon; the second active component is at least one of luteolin, quercetin, quercetin, isoquercetin, naringin, rutin, baicalin, and flavonols; the total mass of the second active components in the third modified solution is 1-2% of the mass of the activated carbon; and the activated carbon is immersed in the third modified solution for 12 to 24 hours by an equal volume impregnation method.

[0020] Tea polyphenols have strong antioxidant ability, can effectively capture and neutralize free radicals, help improve the stability of the catalyst, and reduce the activity loss caused by oxidation during use; tea polyphenols can interact with the surface of activated carbon, change its surface properties, increase the hydrophilicity and reactivity of the activated carbon surface, and help improve the adsorption and reaction efficiency of H2S and COS; the polyhydroxy structure in the tea polyphenol molecule can interact with the molecules of gaseous pollutants (such as H2S), and enhance the adsorption capacity of these gases through hydrogen bonds and other van der Waals forces.

[0021] Caffeine has strong complexing ability and can form stable complexes with metal ions, thereby improving the dispersion and stability of metal active centers, and helping to enhance the catalytic activity of the catalyst in the desulfurization process; caffeine molecules can increase the active sites on the surface of activated carbon, making it more conducive to the adsorption and reaction of gaseous pollutants.

[0022] Similar to tea polyphenols, flavonoids also have strong antioxidant capacity, which can protect the catalyst from oxidative damage and extend its service life; flavonoids can form a complex network structure with the surface of activated carbon through their unique chemical structure, which can promote the adsorption and decomposition reactions of H2S and COS; flavonoids can synergize with other active components (such as metal oxides, pyridine N) to enhance the overall catalytic performance of the catalyst; the glycoside form of flavonoids increases its water solubility and improves the dispersibility and uniformity of these active ingredients in the third modified solution, thereby improving the modification effect; flavonoids in the glycoside form are more stable during heat treatment and can be more evenly distributed on the surface of activated carbon, further improving the performance of the catalyst.

[0023] As a further improvement of the preparation method of the above-mentioned bifunctional desulfurization catalyst: the preparation method of activated carbon comprises the following steps:

[0024] ball-milling tea powder and / or coffee powder, primary carbonized material and first adhesive solution to obtain a mixed material;

[0025] The mixed material, the reinforcing resin powder and the second binder solution are ball-milled and mixed, and then extruded to obtain a compact;

[0026] The pressed green body is activated to obtain activated carbon;

[0027] The fluidity of the first adhesive is 20-50 mPa·s; and the bonding strength of the second adhesive solution is 2-3.5 MPa.

[0028] The applicant has found that in the process of preparing activated carbon, the fluidity and bonding strength of the adhesive solution are two key parameters that significantly affect the quality and performance of the activated carbon. It has been found through experiments that when the fluidity of the first adhesive solution is high, it can ensure that it can fully penetrate and coat the tea powder and / or coffee powder and the primary carbonized material to form a uniform mixture, which is particularly important for the strength of the activated carbon; at the same time, when the bonding strength of the second adhesive solution is high, it can ensure that a green body with sufficient mechanical strength is formed during the green compacting process, thereby ensuring the strength of the activated carbon. Therefore, the present invention significantly improves the compressive strength of the activated carbon by improving the fluidity and bonding strength of the first adhesive solution and the second adhesive solution.

[0029] The present invention adds tea powder and / or coffee powder to the mixture, preferably waste residue powder, to reduce solid waste and improve resource utilization. Tea powder and / or coffee powder are rich in cellulose, minerals, trace elements and organic compounds, which can form more complex and diverse pore structures and a large number of oxygen-containing functional groups (such as carboxyl, hydroxyl, phenolic hydroxyl, etc.) during the activation process. The complex and diverse pore structures are conducive to the subsequent loading of active components. A large number of oxygen-containing functional groups form active sites, which can improve the hydrophilicity and adsorption capacity of activated carbon, and can retain certain bioactive components such as tea polyphenols and caffeine. These bioactive components have antioxidant and antibacterial properties, which can give activated carbon additional functional properties.

[0030] The present invention adds reinforced resin powder to the green body, which can improve the mechanical strength of the activated carbon material and make it more resistant to wear and cracking during use; the reinforced resin powder can improve the molding performance of the mixture, provide better adhesion and plasticity during the extrusion molding process, and enable the pressed green body to be molded more evenly and stably; in the subsequent high-temperature activation treatment process, the reinforced resin powder can improve the thermal stability of the material and reduce the damage to the material structure caused by the high-temperature treatment, thereby maintaining the structural integrity and pore structure richness of the activated carbon; the reinforced resin powder may also have certain chemical properties, and can form a more stable combination with active components such as metal oxides, tea polyphenols and / or caffeine, flavonoid compounds, etc., thereby improving the adsorption performance of the final activated carbon.

[0031] As a further improvement of the preparation method of the above-mentioned bifunctional desulfurization catalyst: the first adhesive solution is an aqueous solution of at least one of sodium carboxymethyl cellulose, polyethylene oxide, hydroxypropyl methyl cellulose, methyl cellulose, hydroxyethyl cellulose, gum arabic, and xanthan gum; 200 to 400 mL of the first adhesive solution is added to every 1 kg of the carbonized material.

[0032] As a further improvement of the preparation method of the above-mentioned bifunctional desulfurization catalyst: the second adhesive solution is an aqueous solution of at least one of syrup, starch paste, polyvinyl alcohol, chitosan, white latex, and dextrin; 100 to 300 mL of the second adhesive solution is added to every 1 kg of the mixture.

[0033] In order to achieve the above object, according to the second aspect of the present invention, a bifunctional desulfurization catalyst is provided, and the technical scheme is as follows:

[0034] The bifunctional desulfurization catalyst is prepared by the preparation method described in the first aspect above.

[0035] In order to achieve the above object, according to the third aspect of the present invention, a flue gas desulfurization method is provided, and the technical scheme is as follows:

[0036] The flue gas desulfurization method uses the bifunctional desulfurization catalyst prepared by the preparation method described in the first aspect to desulfurize the flue gas.

[0037] It can be seen that the bifunctional desulfurization catalyst of the present invention, its preparation method and application provide an activated carbon with low cost, high strength, good adsorption and catalytic ability, and very suitable for flue gas desulfurization, and its preparation method and application, which effectively solves the technical problems of low cost and low desulfurization efficiency of bifunctional desulfurization catalyst in the prior art.

[0038] The following is a further description of the embodiments of the invention provided in this specification in conjunction with the accompanying drawings and specific implementation methods. Additional aspects and advantages of the embodiments of the invention provided in this specification will be partially given in the following description, and partially will become apparent from the following description, or will be understood through the practice of the embodiments of the invention provided in this specification. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The drawings that constitute part of the embodiments of the inventions provided in this specification are used to assist in understanding the embodiments of the inventions provided in this specification. The contents provided in the drawings and their related descriptions in the embodiments of the inventions provided in this specification can be used to explain the embodiments of the inventions provided in this specification, but do not constitute improper limitations on the embodiments of the inventions provided in this specification.

[0040] Figure 1 It is a schematic structural diagram of a desulfurization effect evaluation device of a dual-function desulfurization catalyst of the present invention.

[0041] Figure 2 This is a SEM photograph of the bifunctional desulfurization catalyst of Example 4 of the present invention.

[0042] Figure 3 This is the pore size distribution diagram of the bifunctional desulfurization catalyst of Example 4 of the present invention.

[0043] Figure 1 The reference numerals in the drawings are: 100 - mass flow meter, 200 - mixer, 300 - humidifier, 400 - desulfurization reactor, 410 - heater, 500 - dryer, 600 - gas chromatograph, 700 - tail gas absorption bottle, 800 - three-way valve. DETAILED DESCRIPTION

[0044] The following is a clear and complete description of the embodiments of the inventions provided in this specification in conjunction with the accompanying drawings. A person of ordinary skill in the art will be able to implement the embodiments of the inventions provided in this specification based on these descriptions. Before describing the embodiments of the inventions provided in this specification in conjunction with the accompanying drawings, it should be particularly noted that:

[0045] The technical solutions and technical features provided in each part of the embodiments of the invention provided in this specification, including the following description, may be combined with each other if there is no conflict.

[0046] In addition, the embodiments of the inventions provided in this specification involved in the following descriptions are generally only part of the embodiments of the inventions provided in this specification rather than all of the embodiments. Therefore, based on the embodiments of the inventions provided in this specification, all other embodiments obtained by ordinary technicians in this field without making any creative work should fall within the scope of protection of the embodiments of the inventions provided in this specification.

[0047] Regarding the terms and units in the embodiments of the inventions provided in this specification: The terms "including", "comprising", "having" and any variations thereof in the descriptions and claims of the embodiments of the inventions provided in this specification and in the related parts are intended to cover non-exclusive inclusions. In addition, other relevant terms and units in the embodiments of the inventions provided in this specification can be reasonably interpreted based on the relevant contents of the embodiments of the inventions provided in this specification.

[0048] Figure 1 It is a schematic structural diagram of a desulfurization effect evaluation device of a dual-function desulfurization catalyst of the present invention.

[0049] like Figure 1 As shown in the figure, the method of using the desulfurization effect evaluation device is as follows: first, use N2 to purge the gas in the pipeline to facilitate the test. The mass flow meter 100 at the rear end of the gas cylinder adjusts the flow of the three gases (N2, O2 and COS), and then the three gases are evenly mixed in the mixer 200 to obtain a mixed gas. The COS concentration in the mixed gas is 2000ppm, the volume fraction of O2 is 1vol%, and the gas hourly space velocity is 20000 h -1 . The humidifier 300 (equipped with a water bath heating to generate water vapor) is adjusted so that the moisture content of the mixed gas is 3.1 vol%. The desulfurization reactor 400 is equipped with a heater 410, and the humidified mixed gas is passed into the desulfurization reactor 400 equipped with a dual-function desulfurization catalyst to carry out a desulfurization reaction at 70°C. The desulfurized tail gas is dried by a dryer 500 and the COS and H2S concentrations are monitored and recorded using a gas chromatograph 600 (HF-901 gas chromatograph, Shandong Huifen Instrument Co., Ltd.). The tail gas detected by the gas chromatograph 600 is treated by a tail gas absorption bottle 700 and then discharged. The desulfurization circuit and the non-desulfurization circuit are switched by a three-way valve 800.

[0050] As the reaction proceeds, the removal rates of COS and H2S gradually decrease until breakthrough occurs. The breakthrough time is defined as the time when the removal rate drops to 90% of the original removal rate, recorded as T90. The amount of COS converted or absorbed by the bifunctional desulfurization catalyst within the time of reaching T90 is defined as the breakthrough capacity.

[0051] Example 1: A bifunctional desulfurization catalyst and a preparation method thereof include the following steps:

[0052] Tea powder, coffee powder, primary carbonized material and first adhesive solution are ball-milled to obtain a mixture. The first adhesive is a hydroxypropyl methylcellulose solution with a fluidity of 40 mPa·s. 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The total amount of tea powder and coffee powder is 6% of the amount of the primary carbonized material. The mass of the tea powder and coffee powder is equal, and the particle size of the tea powder and coffee powder is 50 to 200 nm. The primary carbonized material is obtained by grinding and sieving bamboo after carbonizing at 550°C for 2 hours without oxygen.

[0053] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a chitosan solution with a bonding strength of 2.5 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is a phenolic resin, and its amount is 2% of the amount of the mixed material.

[0054] The pressed green body was activated in a steam atmosphere at 900°C for 2 h to obtain activated carbon.

[0055] The activated carbon was immersed in the first modification solution, and after the immersion, it was filtered, dried and heat treated. The first modification solution was a mixed solution of urea and copper nitrate, the mass ratio of nitrogen element to copper element was 1.33:1, and the concentration of nitrogen element was 44.9g / L; the activated carbon was immersed in the first modification solution for 2 hours by using the equal volume impregnation method; the heat treatment temperature was 400℃, and the heat treatment time was 5 hours.

[0056] The activated carbon is immersed in the second modification solution, and after the immersion is completed, it is filtered, dried and heat-treated. The second modification solution is a potassium hydroxide solution, and the mass ratio of potassium hydroxide to activated carbon is 3.4:100; the activated carbon is immersed in the second modification solution for 8 hours by an equal volume impregnation method; the heat treatment temperature is 120°C, and the heat treatment time is 24 hours.

[0057] The activated carbon is immersed in the third modified solution, and after the immersion is completed, it is filtered and dried to obtain a dual-functional desulfurization catalyst. The third modified solution contains a first active component and a second active component; the first active component is tea polyphenols and caffeine, the total mass of the first active component is 1% of the mass of the activated carbon, and the mass of tea polyphenols and caffeine is equal; the second active component is an ethanol solution of quercetin and quercetin, the total mass of the second active component is 1% of the mass of the activated carbon, and the mass of quercetin and quercetin is equal. The activated carbon is immersed in the third modified solution for 12 hours by an equal volume impregnation method.

[0058] The obtained bifunctional desulfurization catalyst has a compressive strength of 255 N / cm, an iodine value of 996 mg / g, and a penetration capacity of 445 mg / g.

[0059] Example 2: A bifunctional desulfurization catalyst and a preparation method thereof include the following steps:

[0060] Tea powder, coffee powder, primary carbonized material and first adhesive solution are ball-milled and mixed to obtain a mixture. The first adhesive is a gum arabic solution with a fluidity of 20 mPa·s, and 300 mL of the first adhesive solution is added to every 1 kg of primary carbonized material. The total amount of tea powder and coffee powder is 7% of the amount of primary carbonized material, the mass of tea powder and coffee powder is equal, and the particle size of tea powder and coffee powder is 50 to 200 nm. The primary carbonized material is obtained by grinding and sieving bamboo after anaerobic carbonization at 550°C for 2 hours.

[0061] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a polyvinyl alcohol solution with a bonding strength of 3 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is a polyurethane resin, and its amount is 2% of the amount of the mixed material.

[0062] The pressed green body was activated in a steam atmosphere at 900°C for 2 h to obtain activated carbon.

[0063] The activated carbon was immersed in the first modification solution, and after the immersion, it was filtered, dried and heat treated. The first modification solution was a mixed solution of urea and copper nitrate, the mass ratio of nitrogen element to copper element was 1.30:1, and the concentration of nitrogen element was 57.3g / L; the activated carbon was immersed in the first modification solution for 2 hours by using the equal volume impregnation method; the heat treatment temperature was 600℃, and the heat treatment time was 1 h.

[0064] The activated carbon is immersed in the second modification solution, and after the immersion is completed, it is filtered, dried and heat-treated. The second modification solution is a potassium carbonate solution, and the mass ratio of potassium carbonate to activated carbon is 3.4:100; the activated carbon is immersed in the second modification solution for 8 hours by an equal volume impregnation method; the heat treatment temperature is 140°C, and the heat treatment time is 21 hours.

[0065] The activated carbon is immersed in the third modified solution, and after the immersion is completed, it is filtered and dried to obtain a dual-functional desulfurization catalyst. The third modified solution contains a first active component and a second active component; the first active component is tea polyphenols and caffeine, the total mass of the first active component is 1% of the mass of the activated carbon, and the mass of tea polyphenols and caffeine is equal; the second active component is an ethanol solution of quercetin and quercetin, the total mass of the second active component is 1% of the mass of the activated carbon, and the mass of quercetin and quercetin is equal. The activated carbon is immersed in the third modified solution for 12 hours by an equal volume impregnation method.

[0066] The obtained bifunctional desulfurization catalyst has a compressive strength of 252 N / cm, an iodine value of 1011 mg / g, and a penetration capacity of 434 mg / g.

[0067] Example 3: A bifunctional desulfurization catalyst and a preparation method thereof include the following steps:

[0068] Tea powder, coffee powder, primary carbonized material and first adhesive solution are ball-milled and mixed to obtain a mixture. The first adhesive is a xanthan gum solution with a fluidity of 50 mPa·s, and 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The total amount of tea powder and coffee powder is 2% of the amount of the primary carbonized material, the mass of the tea powder and the coffee powder are equal, and the particle size of the tea powder and the coffee powder is 50 to 200 nm. The primary carbonized material is obtained by grinding and sieving bamboo after anaerobic carbonization at 550°C for 2 hours.

[0069] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a white latex solution with a bonding strength of 3.5 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is an epoxy resin, and its amount is 1% of the amount of the mixed material.

[0070] The pressed green body was activated in a steam atmosphere at 900°C for 2 h to obtain activated carbon.

[0071] The activated carbon was immersed in the first modification solution, and after the immersion, it was filtered, dried and heat treated. The first modification solution was a mixed solution of urea and ferric nitrate, the mass ratio of nitrogen to iron was 1.17:1, and the concentration of nitrogen was 45.1 g / L; the activated carbon was immersed in the first modification solution for 2 hours by the equal volume impregnation method; the heat treatment temperature was 400°C, and the heat treatment time was 1 h.

[0072] The activated carbon is immersed in the second modification solution, and after the immersion is completed, it is filtered, dried and heat-treated. The second modification solution is a sodium carbonate solution, and the mass ratio of sodium carbonate to activated carbon is 1.71:100; the activated carbon is immersed in the second modification solution for 8 hours by an equal volume impregnation method; the heat treatment temperature is 180°C, and the heat treatment time is 9 hours.

[0073] The activated carbon is immersed in the third modified solution, and after the immersion is completed, it is filtered and dried to obtain a dual-functional desulfurization catalyst. The third modified solution contains a first active component and a second active component; the first active component is tea polyphenols and caffeine, the total mass of the first active component is 1% of the mass of the activated carbon, and the mass of tea polyphenols and caffeine is equal; the second active component is an ethanol solution of rutin and baicalin, the total mass of the second active component is 1% of the mass of the activated carbon, and the mass of rutin and baicalin is equal. The activated carbon is immersed in the third modified solution for 12 hours by an equal volume impregnation method.

[0074] The obtained bifunctional desulfurization catalyst has a compressive strength of 248 N / cm, an iodine value of 1030 mg / g, and a penetration capacity of 431 mg / g.

[0075] Example 4: A bifunctional desulfurization catalyst and a preparation method thereof include the following steps:

[0076] The tea powder, coffee powder, primary carbonized material and the first adhesive solution are ball-milled to obtain a mixture. The first adhesive is a sodium carboxymethyl cellulose solution with a fluidity of 30 mPa·s. 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The total amount of tea powder and coffee powder is 4% of the amount of the primary carbonized material. The mass of the tea powder and the coffee powder is equal, and the particle size of the tea powder and the coffee powder is 50 to 200 nm. The primary carbonized material is obtained by grinding and sieving bamboo after carbonizing at 550°C for 2 hours without oxygen.

[0077] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a polyvinyl alcohol solution with a bonding strength of 3 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is a phenolic resin, and its amount is 2% of the amount of the mixed material.

[0078] The pressed green body was activated in a steam atmosphere at 900°C for 2 h to obtain activated carbon.

[0079] The activated carbon was immersed in the first modification solution, and after the immersion, it was filtered, dried and heat treated. The first modification solution was a mixed solution of urea and copper nitrate, the mass ratio of nitrogen element to copper element was 2.94:1, and the concentration of nitrogen element was 39.4g / L; the activated carbon was immersed in the first modification solution for 2 hours by using the equal volume impregnation method; the heat treatment temperature was 500℃, and the heat treatment time was 3 hours.

[0080] The activated carbon is immersed in the second modification solution, and after the immersion is completed, it is filtered, dried and heat-treated. The second modification solution is a potassium carbonate solution, and the mass ratio of potassium carbonate to activated carbon is 2.72:100; the activated carbon is immersed in the second modification solution for 8 hours by an equal volume impregnation method; the heat treatment temperature is 160°C, and the heat treatment time is 12 hours.

[0081] The activated carbon is immersed in the third modified solution, and after the immersion is completed, it is filtered and dried to obtain a dual-functional desulfurization catalyst. The third modified solution contains a first active component and a second active component; the first active component is tea polyphenols and caffeine, the total mass of the first active component is 1% of the mass of the activated carbon, and the mass of tea polyphenols and caffeine is equal; the second active component is an ethanol solution of rutin and baicalin, the total mass of the second active component is 1% of the mass of the activated carbon, and the mass of rutin and baicalin is equal. The activated carbon is immersed in the third modified solution for 12 hours by an equal volume impregnation method.

[0082] The obtained bifunctional desulfurization catalyst has a compressive strength of 261 N / cm, an iodine value of 976 mg / g, and a penetration capacity of 453 mg / g.

[0083] Example 5: A bifunctional desulfurization catalyst and a preparation method thereof include the following steps:

[0084] The tea powder, coffee powder, primary carbonized material and the first adhesive solution are ball-milled to obtain a mixture. The first adhesive is a sodium carboxymethyl cellulose solution with a fluidity of 30 mPa·s. 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The total amount of tea powder and coffee powder is 5% of the amount of the primary carbonized material. The mass of the tea powder and the coffee powder is equal, and the particle size of the tea powder and the coffee powder is 50 to 200 nm. The primary carbonized material is obtained by grinding and sieving bamboo after anaerobic carbonization at 550°C for 2 hours.

[0085] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a sugarcane molasses solution with a bonding strength of 1.5 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is an acrylic resin, and its amount is 3% of the amount of the mixed material.

[0086] The pressed green body was activated in a steam atmosphere at 900°C for 2 h to obtain activated carbon.

[0087] The activated carbon was immersed in the first modification solution, and after the immersion, it was filtered, dried and heat treated. The first modification solution was a mixed solution of urea and zinc nitrate, the mass ratio of nitrogen element to zinc element was 1.39:1, and the concentration of nitrogen element was 41.3 g / L; the activated carbon was immersed in the first modification solution for 2 hours by using the equal volume impregnation method; the heat treatment temperature was 600°C, and the heat treatment time was 5 h.

[0088] The activated carbon is immersed in the second modification solution, and after the immersion is completed, it is filtered, dried and heat-treated. The second modification solution is a sodium hydroxide solution, and the mass ratio of sodium hydroxide to activated carbon is 1.71:100; the activated carbon is immersed in the second modification solution for 8 hours by an equal volume impregnation method; the heat treatment temperature is 200°C, and the heat treatment time is 3 hours.

[0089] The activated carbon is immersed in the third modified solution, and after the immersion is completed, it is filtered and dried to obtain a dual-functional desulfurization catalyst. The third modified solution contains a first active component and a second active component; the first active component is tea polyphenols and caffeine, the total mass of the first active component is 1% of the mass of the activated carbon, and the mass of tea polyphenols and caffeine is equal; the second active component is an aqueous solution of naringin and baicalin, the total mass of the second active component is 1% of the mass of the activated carbon, and the mass of naringin and baicalin is equal. The activated carbon is immersed in the third modified solution for 12 hours by an equal volume impregnation method.

[0090] The obtained bifunctional desulfurization catalyst has a compressive strength of 244 N / cm, an iodine value of 1082 mg / g, and a penetration capacity of 419 mg / g.

[0091] Example 6: A bifunctional desulfurization catalyst and a preparation method thereof include the following steps:

[0092] The tea powder, the primary carbonized material and the first adhesive solution are ball-milled to obtain a mixture. The first adhesive is a hydroxyethyl cellulose solution with a fluidity of 30 mPa·s, and 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The amount of tea powder used is 3% of the amount of the primary carbonized material, and the particle size of the tea powder is 50 to 200 nm. The primary carbonized material is obtained by grinding and sieving bamboo after carbonizing at 550°C for 2 hours without oxygen.

[0093] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a dextrin solution with a bonding strength of 2 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is a polystyrene resin, and its amount is 2% of the amount of the mixed material.

[0094] The pressed green body was activated in a steam atmosphere at 900°C for 2 h to obtain activated carbon.

[0095] The activated carbon was immersed in the first modification solution, and after the immersion, it was filtered, dried and heat treated. The first modification solution was a mixed solution of urea and ferric nitrate, the mass ratio of nitrogen to iron was 1.77:1, and the concentration of nitrogen was 32.3 g / L; the activated carbon was immersed in the first modification solution for 2 hours by using the equal volume impregnation method; the heat treatment temperature was 500°C, and the heat treatment time was 3 hours.

[0096] The activated carbon is immersed in the second modification solution, and after the immersion is completed, it is filtered, dried and heat-treated. The second modification solution is a sodium carbonate solution, and the mass ratio of sodium carbonate to activated carbon is 1.71:100; the activated carbon is immersed in the second modification solution for 8 hours by an equal volume impregnation method; the heat treatment temperature is 160°C, and the heat treatment time is 15 hours.

[0097] The activated carbon is impregnated in the third modified solution, and after the impregnation is completed, it is filtered and dried to obtain a bifunctional desulfurization catalyst. The third modified solution contains a first active component and a second active component; the first active component is tea polyphenols, and the total mass of the first active component is 1% of the mass of the activated carbon; the second active component is an ethanol solution of luteolin and naringin, and the total mass of the second active component is 1% of the mass of the activated carbon, and the masses of luteolin and naringin are equal. The activated carbon is immersed in the third modified solution for 12 hours by an equal volume impregnation method.

[0098] The obtained bifunctional desulfurization catalyst has a compressive strength of 247 N / cm, an iodine value of 1055 mg / g, and a penetration capacity of 429 mg / g.

[0099] Example 7: A bifunctional desulfurization catalyst and a preparation method thereof include the following steps:

[0100] The coffee powder, the primary carbonized material and the first adhesive solution are ball-milled to obtain a mixture. The first adhesive is a hydroxyethyl cellulose solution with a fluidity of 30 mPa·s, and 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The amount of coffee powder used is 5% of the amount of the primary carbonized material, and the particle size of the coffee powder is 50 to 200 nm. The primary carbonized material is obtained by grinding and sieving bamboo after carbonizing at 550°C for 2 hours without oxygen.

[0101] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a starch paste solution with a bonding strength of 2MPa; 200mL of the second adhesive solution is added to every 1kg of the mixed material. The reinforcing resin powder is a polypropylene resin, and its amount is 3% of the amount of the mixed material.

[0102] The pressed green body was activated in a steam atmosphere at 900°C for 2 h to obtain activated carbon.

[0103] The activated carbon was immersed in the first modification solution, and after the immersion, it was filtered, dried and heat treated. The first modification solution was a mixed solution of urea and zinc nitrate, the mass ratio of nitrogen element to zinc element was 2.25:1, and the concentration of nitrogen element was 35.8g / L; the activated carbon was immersed in the first modification solution for 2 hours by using the equal volume impregnation method; the heat treatment temperature was 500℃, and the heat treatment time was 3h.

[0104] The activated carbon is immersed in the second modification solution, and after the immersion is completed, it is filtered, dried and heat-treated. The second modification solution is a potassium hydroxide solution, and the mass ratio of potassium hydroxide to activated carbon is 3.4:100; the activated carbon is immersed in the second modification solution for 8 hours by an equal volume impregnation method; the heat treatment temperature is 160°C, and the heat treatment time is 18 hours.

[0105] The activated carbon is impregnated in the third modified solution, filtered and dried after the impregnation is completed, and a dual-functional desulfurization catalyst is obtained. The third modified solution contains a first active component and a second active component; the first active component is caffeine, and the total mass of the first active component is 1% of the mass of the activated carbon; the second active component is an ethanol solution of luteolin and naringin, and the total mass of the second active component is 1% of the mass of the activated carbon, and the masses of luteolin and naringin are equal. The activated carbon is immersed in the third modified solution for 12 hours using an equal volume impregnation method.

[0106] The obtained bifunctional desulfurization catalyst has a compressive strength of 245 N / cm, an iodine value of 1143 mg / g, and a penetration capacity of 423 mg / g.

[0107] An embodiment of the flue gas desulfurization method of the present invention is to prepare a dual-function desulfurization catalyst using the preparation method described in any one of the above embodiments to perform desulfurization treatment on the flue gas.

[0108] Comparative Example 1: Compared with Example 4, the bifunctional desulfurization catalyst and its preparation method of this comparative example are different in that tea powder and coffee powder are not used. The obtained bifunctional desulfurization catalyst has a compressive strength of 265N / cm, an iodine value of 966mg / g, and a penetration capacity of 440mg / g.

[0109] Comparative Example 2: Compared with Example 4, the bifunctional desulfurization catalyst and its preparation method of this comparative example are different in that the third modification solution is not used for impregnation modification. The obtained bifunctional desulfurization catalyst has a compressive strength of 262N / cm, an iodine value of 941mg / g, and a penetration capacity of 432mg / g.

[0110] Comparative Example 3: Compared with Example 4, the bifunctional desulfurization catalyst and its preparation method of this comparative example are different in that no reinforcing resin powder is used. The compressive strength of the obtained bifunctional desulfurization catalyst is 239N / cm, the iodine value is 973mg / g, and the penetration capacity is 443mg / g.

[0111] Comparative Example 4: Compared with Example 2, the bifunctional desulfurization catalyst and its preparation method in this comparative example have the following differences: the first adhesive is a gum arabic solution with a fluidity of 15 mPa·s. The obtained bifunctional desulfurization catalyst has a compressive strength of 239 N / cm, an iodine value of 995 mg / g, and a penetration capacity of 421 mg / g.

[0112] Comparative Example 5: Compared with Example 3, the bifunctional desulfurization catalyst and its preparation method in this comparative example have the following differences: the first adhesive is a polyethylene oxide solution with a fluidity of 55 mPa·s. The obtained bifunctional desulfurization catalyst has a compressive strength of 229 N / cm, an iodine value of 965 mg / g, and a penetration capacity of 423 mg / g.

[0113] Comparative Example 6: Compared with Example 5, the bifunctional desulfurization catalyst and its preparation method of this comparative example have the following differences: the second adhesive solution is a sugarcane molasses solution, and the bonding strength is 1.2 MPa. The compressive strength of the obtained bifunctional desulfurization catalyst is 226 N / cm, the iodine value is 987 mg / g, and the penetration capacity is 414 mg / g.

[0114] Comparative Example 7: Compared with Example 3, the bifunctional desulfurization catalyst and its preparation method in this comparative example have the following differences: the second adhesive solution is a white latex solution, and the bonding strength is 3.7 MPa. The compressive strength of the obtained bifunctional desulfurization catalyst is 262 N / cm, the iodine value is 969 mg / g, and the penetration capacity is 421 mg / g.

[0115] Figure 2 This is a SEM photo of the bifunctional desulfurization catalyst of Example 4 of the present invention. Figure 2 As shown, the bifunctional desulfurization catalyst has a porous structure.

[0116] Figure 3 : is the pore size distribution diagram of the dual-function desulfurization catalyst of Example 4 of the present invention. Figure 3 As shown, the bifunctional desulfurization catalyst has a hierarchical pore distribution, including ultramicropores at 0.5 nm, micropores at 1.3 nm and mesopores at 13 nm. The ultramicropores are conducive to oxygen activation, the micropores are conducive to the dispersion reaction of active sites, and the mesopores are conducive to the storage of desulfurization products.

[0117] The fluidity of the adhesive is tested using the "Method for Determination of Viscosity of Adhesives" (GB / T 2794-2022). The higher the viscosity value, the lower the fluidity.

[0118] The bonding strength of the adhesive is tested using the "Determination of tensile shear strength of adhesives (rigid material to rigid material)" (GB / T 7124-2008). The greater the tensile shear strength value, the greater the bonding strength.

[0119] The compressive strength was tested using the “Test method for wood activated carbon - Determination of strength” (GB / T 12496.6-1999).

[0120] The iodine value test is carried out according to the "Test method for wood activated carbon - Determination of iodine adsorption value" (GB / T 12496.8-1999).

[0121] The above is a description of the relevant contents of the embodiments of the inventions provided in this specification. Based on these descriptions, a person of ordinary skill in the art will be able to implement the embodiments of the inventions provided in this specification. Based on the above contents of the embodiments of the inventions provided in this specification, all other preferred implementations and embodiments obtained by a person of ordinary skill in the art without making any creative work shall fall within the scope of protection of the embodiments of the inventions provided in this specification.

Claims

1. A method for preparing a bifunctional desulfurization catalyst, wherein the bifunctional desulfurization catalyst is used for removing COS and H2S from flue gas at low temperature, and is characterized in that: The preparation method comprises the following steps: The activated carbon is immersed in a first modification solution, and after the immersion is completed, the activated carbon is filtered, dried and heat-treated; the first modification solution contains urea and at least one of a soluble copper salt, an iron salt and a zinc salt; The activated carbon is impregnated in a second modification solution, and after the impregnation, the activated carbon is filtered, dried and heat treated; the second modification solution contains an alkali metal salt and / or a base; The activated carbon is immersed in a third modified solution, and after the immersion is completed, it is filtered and dried to obtain a bifunctional desulfurization catalyst; the third modified solution contains a first active component and / or a second active component, the first active component is tea polyphenols and / or caffeine, and the second active component is a flavonoid compound or a glycoside of a flavonoid compound; The method for preparing activated carbon comprises the following steps: ball-milling tea powder and / or coffee powder, primary carbonized material and first adhesive solution to obtain a mixed material; The mixed material, the reinforcing resin powder and the second binder solution are ball-milled and then extruded to obtain a compact; The pressed green body is activated to obtain activated carbon; The fluidity of the first adhesive is 20-50 mPa·s; and the bonding strength of the second adhesive solution is 2-3.5 MPa.

2. The method for preparing a bifunctional desulfurization catalyst according to claim 1, characterized in that: The mass ratio of nitrogen element to metal element in the first modified solution is (1-3):1, and the concentration of nitrogen element is 30-60 g / L; the activated carbon is immersed in the first modified solution for 1-3 hours by using an equal volume impregnation method; the heat treatment temperature is 400-600°C, and the heat treatment time is 1-5 h.

3. The method for preparing a bifunctional desulfurization catalyst according to claim 1, characterized in that: The mass ratio of alkali metal salt and / or base to activated carbon in the second modified solution is (1.5-10):100; the activated carbon is immersed in the second modified solution for 0.5-12 hours by an equal volume impregnation method; the heat treatment temperature is 120-200°C, and the heat treatment time is 3-24 hours; the second modified solution contains at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.

4. The method for preparing a bifunctional desulfurization catalyst according to claim 1, characterized in that: The mass of the first active component in the third modified solution is 1-2% of the mass of the activated carbon; the second active component is at least one of luteolin, quercetin, quercetin, isoquercetin, naringin, rutin, baicalin, and flavonols; the total mass of the second active components in the third modified solution is 1-2% of the mass of the activated carbon; and the activated carbon is immersed in the third modified solution for 12-24 hours using an equal volume impregnation method.

5. The method for preparing a bifunctional desulfurization catalyst according to claim 1, characterized in that: The first adhesive solution is an aqueous solution of at least one of sodium carboxymethyl cellulose, polyethylene oxide, hydroxypropyl methyl cellulose, methyl cellulose, hydroxyethyl cellulose, gum arabic and xanthan gum; 200-400 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material.

6. The method for preparing a bifunctional desulfurization catalyst according to claim 5, characterized in that: The second adhesive solution is an aqueous solution of at least one of syrup, starch paste, polyvinyl alcohol, chitosan, white latex, and dextrin; 100 to 300 mL of the second adhesive solution is added to every 1 kg of the mixture.

7. Dual-function desulfurization catalyst, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.

8. A flue gas desulfurization method, characterized in that: The flue gas is desulfurized using the bifunctional desulfurization catalyst prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Blast furnace gas desulfurization catalyst and blast furnace gas desulfurization process

    CN114768875A

  • Manufacture of gas absorbent

    JP1999009992A

  • KR1018410650000B1